2019
DOI: 10.18546/lre.17.2.04
|View full text |Cite
|
Sign up to set email alerts
|

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement

Abstract: The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
(8 reference statements)
2
16
0
2
Order By: Relevance
“…T45 Course could be extended to more hours so that we have even more knowledge on the subject but also because we had such a nice atmosphere and had such a good time… in a course that was offered for free." educational needs, result which agrees with the findings from Kennedy and Laurillard (2019). Likewise, the satisfaction from the constant encouragement, support and feedback with constructive comments from the instructor was demonstrated in our research as well as in the research of Prestridge and Tondeur (2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…T45 Course could be extended to more hours so that we have even more knowledge on the subject but also because we had such a nice atmosphere and had such a good time… in a course that was offered for free." educational needs, result which agrees with the findings from Kennedy and Laurillard (2019). Likewise, the satisfaction from the constant encouragement, support and feedback with constructive comments from the instructor was demonstrated in our research as well as in the research of Prestridge and Tondeur (2015).…”
Section: Discussionsupporting
confidence: 89%
“…Recently MOOCs addressed teachers (online Teacher Professional Development -oTPD) giving a new dynamic to the field. Research (Kennedy & Laurillard, 2019;Κoukis & Jimoyiannis, 2017Κoukis & Jimoyiannis, , 2019 has shown that teachers are satisfied with the design and the implementation of TPD -MOOCs and Yoo (2016) argues that the involvement of teachers in online experiences of professional development programs improves their self-efficacy. According to Cho and Rathbun (2013) the asynchronous discussions that take place in MOOCs improve the active participation and allow the creation of self-controlled and self-directed learning environments and Rahimi, Henze, Hermans, and Barendsen (2018) state that MOOCs can link educational content to the curriculum.…”
Section: / 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher education research has looked at various elements associated with teacher development. For example, Kennedy and Laurillard ( 2019 ) examined the use of co-design models in MOOC projects to deliver teacher professional development (TPD) and developed a ToC model that could be applied to TPD for mass displacement, which could assist in the professional development needs of MOOC teachers with MOOC in mass displacement. Course gamification and recommendation research has mainly examined the elements associated with MOOC course improvements, such as gamification and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the potential of MOOCs and digital tools to target populations, which do not form part of localised networks, has been increasingly explored. For example, recent work by Kennedy and Laurillard (2019) shows the challenges and opportunities for co-designing digital technologies to provide teacher professional education in the context of mass displacement. The large scale and wide reach of these technologies as well as their ability to accommodate localized context as well as generic principles, have implications for re-dressing especially the unequal distribution of access to education.…”
Section: Alternative Networkmentioning
confidence: 99%